Use of a proline-specific endopeptidase to reintroduce gluten in patients with non-coeliac gluten sensitivity: A randomized trial. Issue 9 (September 2022) - Scricciolo, A.; Lombardo, V.; Elli, L.; Bascuñán, K.A.; Doneda, L.; Rinaldi, F.; Pinto, D.; Araya, M.; Costantino, A.; Vecchi, M.; Roncoroni, L.
Summary: Background: A gluten-free diet (GFD) is the main therapy for non-coeliac gluten sensitivity (NCGS). However, the availability of novel enzymes with the ability to digest gluten could represent a therapeutic opportunity for NCGS patients to avoid a GFD. Aims: To evaluate the controlled reintroduction of gluten with or without the endopeptidase P1016 in NCGS patients. Methods: This is a randomized, double-blind, placebo-controlled monocentric study, Registered under ClinicalTrials.gov Identifier no. NCT01864993. Gluten was reintroduced incrementally over a 3-week period under nutritional control. NCGS patients were randomized into two groups and administered P1016 or placebo during gluten reintroduction. We evaluated symptoms (visual analogue scale, VAS), quality of life (SF-36) and mental health symptoms (SCL-90) on a weekly basis. Results: We enrolled a total 23 patients who were allocated to a placebo group (n = 11, age 38.4 ± 2.9) or an intervention group (n = 12, age 39.5 ± 3.1). No effect of P1016 on symptoms was found. During gluten reintroduction, patients reported a significant increase in abdominal pain and a worsening of stool consistency. Furthermore, no differences were found between the groups regarding SCL-90 and SF-36 scores. Conclusions: Our results demonstrate a lack of effect of P1016 in the management of NCGS patients and the possible reintroduction of gluten.